Child Deaths due to Neglect - Pakiş, Işıl; Yaycı, Nesime Okboy; Günçe, Elif; Çelik, Safa; Uysal, Cem; Karapirli, Mustafa (The Bulletin of Legal Medicine, 2008)
Child neglect or passive child abuse can be defined as failure to provide for the child’s basic needs or disregard to care which results in serious harm. Although neglect is the most common form of child abuse, it is rarely diagnosed properly. The number of neglect cases referred to the judicial system is limited, as well. Since neglect cases are not identified and diagnosed easily, their mortality rates seem to be low. On the basis of venue, history, postmortem external and internal as well as microscopical examinations 4 cases between 2 months and 3 years of age, autopsi-ed at the Council of Forensic Medicine Morgue Department were evaluated regarding child abuse and neglect. In three of the cases, height and weight was found lower than the growth percentiles established by Istanbul Medical Faculty. In three cases general hygiene was poor and turgor tonus was diminished. Description of the venue; case, family and medical history are of critical importance in cases claimed to be neglect or abuse. Postmortem examination should include detailed external and internal examinations, appropriate microscopical sampling and supportive tests. Key words: Child, neglect, death, abuse